2000
DOI: 10.1073/pnas.200240897
|View full text |Cite
|
Sign up to set email alerts
|

The state diagram for cell adhesion under flow: Leukocyte rolling and firm adhesion

Abstract: Leukocyte adhesion under flow in the microvasculature is mediated by binding between cell surface receptors and complementary ligands expressed on the surface of the endothelium. Leukocytes adhere to endothelium in a two-step mechanism: rolling (primarily mediated by selectins) followed by firm adhesion (primarily mediated by integrins). Using a computational method called ''Adhesive Dynamics,'' we have simulated the adhesion of a cell to a surface in flow, and elucidated the relationship between receptorligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
226
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(240 citation statements)
references
References 44 publications
11
226
1
1
Order By: Relevance
“…5). These parameters are consistent with the function of avidin-biotin known to mediate firm adhesion under flow (33).…”
Section: Mapping the Deadhesion Energy Landscape Under A Mechanical Fsupporting
confidence: 84%
See 1 more Smart Citation
“…5). These parameters are consistent with the function of avidin-biotin known to mediate firm adhesion under flow (33).…”
Section: Mapping the Deadhesion Energy Landscape Under A Mechanical Fsupporting
confidence: 84%
“…Fig. 4 also shows the force spectra for two representative cases of two other protein͞ligand pairs that mediate different dynamic states of adhesion of a cell under a hydrodynamic flow: L-selectin or P-selectin͞PSGL-1 that mediate the so-called rolling adhesion (33), and avidin͞ biotin, which mediates firm cell adhesion, as reported by Evans et al (34) and by Merkel et al (35), respectively. Unlike the plot obtained here for the Fn͞Fn-adhesin interaction, which shows a single linear regime, these two plots reveal two distinct linear regimes.…”
Section: Mapping the Deadhesion Energy Landscape Under A Mechanical Fmentioning
confidence: 75%
“…A key molecule in this process is L-selectin, a leukocyte-expressed adhesion receptor that is localized to tips of microvilli and binds to glycosylated ligands on the endothelium. Its properties are optimized for initial capture and rolling under physiological shear (2,3), as confirmed by recent experimental data and computer simulations (4,5). In contrast to tethering through other receptor systems like P-selectin, E-selectin, or integrins, appreciable tethering through L-selectin and subsequent rolling occurs only above a threshold in shear (6), even in cell-free systems (7,8).…”
mentioning
confidence: 75%
“…Adhesive dynamics has been used extensively to investigate the biophysics of cell adhesion (28,29), and we recently demonstrated that integrating catch-slip mechanochemistry can account for shear-promoted rolling behavior (30). We first evaluated the ability of each parameter set to accurately predict the rolling dynamics of human neutrophils on a PSGL-1 substrate observed from 0 to 2 dynes/cm 2 wall shear stress.…”
Section: Predicting Selectin-mediated Adhesion Dynamicsmentioning
confidence: 99%